The adaptation problem, evolution and normative economics - Mozaffar Qizilbash (Max Planck Institute of Economics, 2007)
Amartya Sen has advanced a number of distinct arguments against utilitarianism and 'utility'-based views more generally. One of these invokes various ways in which underdogs can 'adapt' and learn to live with their situations. Sen's argument is related to Jon Elster's discussion of 'adaptive preferences' but is distinct in part because Sen cites the need for underdogs to survive. When read in combination with his discussion of Darwinism, Sen's discussion of adaptation is relevant to recent work in normative economics which is influenced by evolutionary biology. It poses a problem for Richard Layard's book on happiness, particularly its policy conclusions. It also poses a problem for Ken Binmore's account of justice because the empathetic preferences in terms of which interpersonal comparisons are made in Binmore's account are formed through social evolution.
Keywords: 330; adaptation; preferences; utilitarianism; capability; evolution; happiness; Präferenztheorie; Anpassung; Utilitarismus; Evolutionsökonomik; Lebenszufriedenheit; Kritik; Theorie